NATIONAL CULTURAL VALUES IN THE CONTENT OF EDUCATION - Botirova Mukarram (Galaxy International Interdisciplinary Research Journal, 2022)
This article clearly shows the importance of raising children from the hadith of the Prophet (peace and blessings of Allah be upon him), from hadiths and demonstrative stories. It was noted here that children's education consists of several stages and aspects. There are many recommendations and instructions on this subject from the Holy Quran and hadiths.